Immunotherapy in advanced cutaneous melanoma patients - Mackiewicz, Jacek; Krokowicz, Łukasz (Menopause Review/Przegląd Menopauzalny, 2013)
The incidence of cancer has been increasing worldwide. Melanoma is known to be one of the most immunogenic malignancies in humans. In recent years innovative and promising therapeutic strategies that modulate the immune response or target various intracellular pathways in melanoma have been developed. Recently new drugs which improved overall survival in phase III regulatory studies namely, ipilimumab (anti-CTLA-4 antibody) and vemurafenib (BRAF inhibitor) have been approved in Europe and the USA, and so has a combination of dabrafenib (BRAF inhibitor) and trametinib (MEK inhibitor) in the USA for the treatment of metastatic melanoma. A number of novel immunotherapy strategies including anti-PD-1, anti-PD-1L or cancer vaccines show a durable high response rate in advanced melanoma patients, however efficacy of these drugs needs to be confirmed in phase III studies. Results from preclinical studies and early clinical trials indicate a high potential for combining immunotherapy with other treatment strategies – currently many new drug combinations are being evaluated in phase I or II in patients with metastatic melanoma.